CONFLICT OF INTEREST AND CREDIBILITY OF INVESTMENT BANKS STOCK RECOMMENDATIONS AND EARNINGS FORECASTS: Empirical Evidence of Finnish IPO Market from Years 1996 to 2000 - Maijala, Ville (My University, 2003)
The aim of this research is to investigate if the underwriting investment banks issue more positive stock recommendations and EPS estimates for IPO companies than non-underwriting investment banks. This research will also analyse if the positism in underwriting investment banks recommendations remain one year after the IPO. Furthermore this research will examine the accuracy of underwriting and non-underwriting investment banks EPS forecasts for the IPO year and one year after. This research will compare underwriting and non-underwriting investment banks stock recommendations and EPS forecasts for companies listed in Helsinki Stock Exchange between 1996 and 2000. The empirical results show that the underwriting investment banks issued more positive stock recommendations during the IPO year than non-underwriting investment banks. The results present that 65.7 percent of underwriting and only 20 percent of non-underwriting investment banks recommendations were ´Strong Buy` recommendations. The underwriting investment banks recommendation also remained more positive a year after the IPO. The empirical evidence show that 53 percent of underwriting and 17.6 percent of non-underwriting investment banks recommendations were ´Strong Buy` recommendations. The results also present that the underwriting investment banks issue more positive mean EPS forecasts than non-underwriting investment banks. The positism is evident for the IPO year and for two following years. Statistical significance was found for the two years following the IPO. The positism in mean EPS forecasts remained one year after the IPO. The underwriting investment banks mean EPS forecasts were also less accurate than non-underwriting investment banks forecasts. The non-underwriting mean EPS forecasts were more accurate during the IPO year and one year after.
Keywords: Conflict of interest; analyst bias; IPO; investment bank; underwriting; non-underwriting; Chinese Wall.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|